A Comparative Risk Analysis of Investment Portfolios Consisting of Stocks and Cryptocurrencies Using Value at Risk Method - Na Bangchang, Kannat; Orid, Nontawat; Yosmaek, Jirawat; Panyarod, Juthaporn (Journal of Science Ladkrabang, 2026)
This research examines and compares the risk levels of investment portfolios composed of stocks and cryptocurrencies using the Value at Risk approach. The objective is to evaluate the risk profiles of both asset classes and compare Value at Risk (VaR) estimates calculated through three distinct methodologies: Historical Simulation, Variance-Covariance (Parametric), and Monte Carlo Simulation. The study utilizes daily price fluctuations of ten selected assets, comprising five stocks: BCP, DELTA, ICT, KTB, and TRUE and five cryptocurrencies: TrueUSD (TUSD), Binance Coin (BNB), Ethereum (ETH), Bitcoin (BTC), and Solana (SOL). The analysis is based on an equally weighted portfolio with a total value of 1,000,000 THB. The dataset spans a three-year period from September 1, 2021, to August 31, 2024. The empirical results reveal that at a 90% confidence level, the VaR estimates are 2.88%, 2.04%, and 2.12% for the Historical simulation, Variance–covariance, and Monte Carlo methods, respectively. At the 95% confidence level, the values increase to 4.50%, 3.17%, and 3.34%, while at the 99% confidence level, they reach 9.18%, 5.27%, and 5.39%, respectively. Ultimately, this study suggests that investors can apply VaR techniques to evaluate and compare risks in hybrid portfolios. Such an approach enables more informed decision-making aligned with individual risk tolerance and provides a more precise evaluation of potential financial exposure.